From Sacred to Commodified: The Semantic Transformation of Arabic Language in Indonesian Horror Film Titles - Astari, Rika; Faturrahman, Muhammad Irfan; Darlin, Muhammad Zakaria; Sudaryani, Rina Ratih Sri; Yusroh, Yusroh; Mukhlis, Abdul; Annafiri, Ahmad Zaki (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study examines the use and semantic transformation of Islamic religious language in Indonesian horror films. Findings reveal that desacralizationge with horror themes to attract the predominantly Muslim audience, media commodification has transformed sacred expressions into commercial tools, leading to the distortion of religious literacy and public resistance. The research aims to identify forms of semantic transformation, investigate its causes, and analyze its impact on public discourse and understanding of religious language. Using both primary and secondary data, the study focused on Indonesian horror films released on YouTube between 2019 and 2023. Data were classified based on theories of desacralization and connotative meaning, with analysis encompassing linguistic patterns and audience comments. Findings reveal that semantic transformation arises mainly from the commodification of religion through syncretic storytelling that blends Islamic elements with horror, creating confusion and misinterpretations of Islamic teachings among the public.